ثنائية السلطة التشريعية في تدبير شؤون الأمة (دراسة تحليلية لعلاقة المؤسسة الدينية والسلطة المدنية في ضوء الفقه السياسي) - Saepul Anwar (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2022)
The jurists believe that the authority or the imamate was placed among the nation in order to fulfill the function of prophethood in guarding religion and the politics of the world. This matter can only be achieved if the authority is given to those who have the capacity to manage the affairs of the nation, both religiously and worldly. Among the important matters in managing the affairs of the nation is a legislative matter in legislating laws on which the nation relied in their lives. With the diversity of the affairs of the nation, including what is purely religious, and what is purely worldly, and what is mixed between religious and worldly matters, what has been legislated by the religious institution and what has been proven by the civil authority may be confronted. On this basis, this research proceeds to study the relationship between the religious institution and the civil authority, and how that relationship should be according to Islamic political jurisprudence. Among the hypotheses of this research, the first: that the civil authority, as an official legislative authority, needs to monitor the religious institution so that the laws it legislated do not contradict the religious values that the nation needs. Second: The religious institution, as a religious authority, needs the help of the civil authority to know the reality of the nation in order to achieve the spirit of bringing benefit and warding off corruption in some changing issues related to guarding religion and its lofty values. Third: The relationship between the religious institution and the civil authority in the perspective of Islamic political jurisprudence should be an integrative, cooperative and monitoring relationship in order to achieve the supreme goal of the existence of the authority, which is to bring the interest and ward off corruption to the Islamic community in the light of building security and social stability in order to preserve the protection of religion and worldly politics.